PENGGUNAAN METODE TASK-BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS MAHASISWA - Kusnawati, Tri (Jurnal Pendidikan Bahasa dan Sastra, 2014)
This study aims to increase the writing skills of students of French Education Department of Language and Art Faculty of Yogyakarta State University by using the task-based learning method in Expression Ecrite IV teaching. This is a classroom action research project consisting of two cycles. The subjects’ of the study were 15 students who took Writing IV (Expression Ecrite IV) including the lecturer. Data were collected using a test, an observation, and a questionnaire. The data of the use of teaching method of task-based learning in Expression Ecrite IV obtained by using an observation and a questionnaire was interpreted qualitatively, while the data of students’ learning achievement in writing was analyzed quantitatively. Findings show that the use of learning method of task-based learning in Expression Ecrite IV could increase writing skills of the students. It was shown by the better comprehension and the mastery of materials. It was proven by the increase of the means in the posttest, that were 6.3 in cycle 1 and 7.2 in cycle 2. Besides, there was an improvement of learning process of writing skill IV as indicated by decreasing students’ passivity and increasing participation in meaningful learning activities.